A Model for Assessing the Reuse of an Ancient Place of Performance: The Bouleuterion of Teos. (2nd October 2017) - Çalışkan, Merve
Abstract: Ancient places of performance are often considered for reuse as a means of promoting archaeological sites. Therefore, local authorities and decision makers have a difficult task of balancing the conservation and management of the sites with the carrying capacity. In this paper, the bouleuterion, a 'rediscovered' structure, at the Teos archaeological site, in Turkey is evaluated and presented as a preliminary case study with the hopes that these issues will be taken into consideration by the managing body in the creation of a management plan for the site. The evaluation is made by assessing socio-economic and intangible heritage significance, policies guiding changes at the site, a qualitative survey at the site and by defining the structure's carrying capacity. The site's strengths, weaknesses, opportunities, and threats are used to create criteria and make proposals for its reuse. The study concludes that the bouleuterion cannot be reused as a venue in its present condition and makes recommendations for future use.